Circulating Plasma miRNA and Clinical/Hemodynamic Characteristics Provide Additional Predictive Information About Acute Pulmonary Thromboembolism, Chronic Thromboembolic Pulmonary Hypertension and Idiopathic Pulmonary Hypertension - Fabro, Alexandre Todorovic; Rugolo, Juliana Machado [UNESP]; Baldavira, Camila Machado; Prieto, Tabatha Gutierrez; Farhat, Cecília; Rotea ManGone, Flavia Regina; Batah, Sabrina Setembre; Cruvinel, Heloísa Resende; Aldá, Maiara Almeida; Monteiro, Jhonatas Sirino; Pádua, Adriana Inacio; Morais, Sirlei Siani; et al. (Frontiers, 2021)
Idiopathic pulmonary artery hypertension (IPAH), chronic thromboembolic pulmonary hypertension (CTEPH), and acute pulmonary embolism (APTE) are life-threatening cardiopulmonary diseases without specific surgical or medical treatment. Although APTE, CTEPH and IPAH are different pulmonary vascular diseases in terms of clinical presentation, prevalence, pathophysiology and prognosis, the identification of their circulating microRNA (miRNAs) might help in recognizing differences in their outcome evolution and clinical forms. The aim of this study was to describe the APTE, CTEPH, and IPAH-associated miRNAs and to predict their target genes. The target genes of the key differentially expressed miRNAs were analyzed, and functional enrichment analyses were carried out. The miRNAs were detected using RT-PCR. Finally, we incorporated plasma circulating miRNAs in baseline and clinical characteristics of the patients to detect differences between APTE and CTEPH in time of evolution, and differences between CTEPH and IPAH in diseases form. We found five top circulating plasma miRNAs in common with APTE, CTEPH and IPAH assembled in one conglomerate. Among them, miR-let-7i-5p expression was upregulated in APTE and IPAH, while miRNA-320a was upregulated in CTEP and IPAH. The network construction for target genes showed 11 genes regulated by let-7i-5p and 20 genes regulated by miR-320a, all of them regulators of pulmonary arterial adventitial fibroblasts, pulmonary artery endothelial cell, and pulmonary artery smooth muscle cells. AR (androgen receptor), a target gene of hsa-let-7i-5p and has-miR-320a, was enriched in pathways in cancer, whereas PRKCA (Protein Kinase C Alpha), also a target gene of hsa-let-7i-5p and has-miR-320a, was enriched in KEGG pathways, such as pathways in cancer, glioma, and PI3K-Akt signaling pathway. We inferred that CTEPH might be the consequence of abnormal remodeling in APTE, while unbalance between the hyperproliferative and apoptosis-resistant phenotype of pulmonary arterial adventitial fibroblasts, pulmonary artery endothelial cell and pulmonary artery smooth muscle cells in pulmonary artery confer differences in IPAH and CTEPH diseases form. We concluded that the incorporation of plasma circulating let-7i-5p and miRNA-320a in baseline and clinical characteristics of the patients reinforces differences between APTE and CTEPH in outcome evolution, as well as differences between CTEPH and IPAH in diseases form.
Keywords: blood plasma; microRNA; pulmonary hypertension; RNA-sequencing; thromboemboilc disease